2020
DOI: 10.1007/s10886-020-01222-1
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive and Inducible Resistance to Thrips Do Not Correlate With Differences in Trichome Density or Enzymatic-Related Defenses in Chrysanthemum

Abstract: Western flower thrips (WFT), Frankliniella occidentalis, is a serious insect pest of Chrysanthemum [Chrysanthemum × morifolium Ramat. (Asteraceae)]. Here we have investigated whether genotypic variation in constitutive and inducible resistance to WFT correlates with phenotypic differences in leaf trichome density and the activity of the defense-related enzyme polyphenol oxidase (PPO) in chrysanthemum. Non-glandular and glandular leaf trichome densities significantly varied among ninety-five chrysanthemum culti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…While MeJA application has been described to induce resistance against the two-spotted spider mite (Warabieda et al, 2005), most studies concerning elicitor use in the Rosaceae family frequently evaluated postharvest effects of elicitor treatments rather than defense responses during cultivation. Congruent with the reported effects of JA-mediated plant-induced defenses on thrips in tomato (Chen et al, 2018(Chen et al, , 2020 and chrysanthemum (Escobar-Bravo et al, 2017) showed that thrips feeding damage was significantly reduced upon repeated MeJA foliar sprays during the nursery phase. The three commercial cultivars varied inherently in thrips susceptibility, with the cultivar Delizzimo being more susceptible than the cultivars Elan or Rowena.…”
Section: Discussionmentioning
confidence: 63%
“…While MeJA application has been described to induce resistance against the two-spotted spider mite (Warabieda et al, 2005), most studies concerning elicitor use in the Rosaceae family frequently evaluated postharvest effects of elicitor treatments rather than defense responses during cultivation. Congruent with the reported effects of JA-mediated plant-induced defenses on thrips in tomato (Chen et al, 2018(Chen et al, , 2020 and chrysanthemum (Escobar-Bravo et al, 2017) showed that thrips feeding damage was significantly reduced upon repeated MeJA foliar sprays during the nursery phase. The three commercial cultivars varied inherently in thrips susceptibility, with the cultivar Delizzimo being more susceptible than the cultivars Elan or Rowena.…”
Section: Discussionmentioning
confidence: 63%